Students’ need on basic English grammar teaching material based on interactive multimedia: an innovative design - Tiarina, Yuli; Syarif, Hermawati; Jufrizal, Jufrizal; Rozimela, Yenni (COUNS-EDU: The International Journal of Counseling and Education, 2019)
This article, a part of dissertation entitled  Developing Basic English Grammar Teaching Material based on Interactive Multimedia at University Level, presents the results of a study conducted to find the model of Basic English Grammar teaching material based on interactive multimedia needed by the students. This empirical research employed both quantitative and qualitative analyses. Seventy eight students of English Department of Universitas Negeri Padang were involved. The students  were required to articulate their need on a design of Basic English Grammar teaching material based on interactive multimedia. The data were collected through an open questionnaire. The first result is that Basic English Grammar teaching material based on interactive multimedia is very needed (with the score 3.1 out of 4). Second, the result indicates the organization of Basic English Grammar teaching material based on interactive multimedia. The organization consists of six parts. They are Time to watch/sing/read, Time to chat, Time to Focus, Time for fun practice, Time for tube, and Time for action. Third, the students have different learning style. Fourty two students (53.84%) have visual learning style. Twenty two students (28.21%) have audio learning style. The rest, fourteen students (17.95%) have kinestetic learning style. Four, the finding shows the students have their favorite movies, colors, and music. The students like comedy/humor, drama, horror, dokumentary, and action movies; they love pop, jazz, rock, country, and rap music; they adore blue, green, black, pink, and red color. Another important research finding is almost all students (91%) have their own laptop. Those findings will be considerations in designing the Basic English Grammar teaching material based on interactive multimedia. Further research to see the effectiveness of the model of Basic English Grammar teaching material based on interactive multimedia needs to be done.